The Gẹ̀lẹ̀dé spectacle art, gender and social harmony in an African culture - Lawal, Babatunde (Univ. of Washington Press, 1996)
This remarkable study explores the use of the visual and performing arts to promote nonviolence and social harmony in sub-Saharan Africa. It focuses on Gelede, a popular community festival of masquerade, dance, and song, held several times a year by the Yoruba of Southwestern Nigeria and the Republic of Benin. Lawal bases his book on extensive field research - observations and interviews - conducted over more than two decades as well as on numerous published and unpublished scholarly sources. He casts significant new light on many previously obscure aspects of Gelede, and he demonstrates a useful methodological approach to the study of non-Western art. The Gelede Spectacle is illustrated in color and black-and-white with over 150 field and museum photographs, including a rare sequence on the dressing of a masquerader. It offers, in addition, more than 60 Gelede song texts, proverbs, and divination verses, each in the original Yoruba as well as in translation. Lawal's interpretations of these pieces indicate the rich complexities of metaphor and analogy inherent in the Yoruba language and art.
Keywords: Danse folklorique yorouba; Femmes yorouba - Murs et coutumes; Femmes yoruba - Moeurs et coutumes; Gelede (Rite yorouba); Masques yorouba; Masques yoruba; Yorouba (Peuple d'Afrique) - Murs et coutumes; Yorouba (Peuple d'Afrique) - Rites et cérémonies; Yoruba (peuple d'Afrique) - Rites et cérémonies; Alltag, Brauchtum; Folk dancing, Yoruba; Gelede (Yoruba rite); Masks, Yoruba; Women, Yoruba -- Social life and customs; Yoruba (African people) -- Rites and ceremonies; Yoruba (African people) -- Social life and customs; Brauch; Ritual; Frau; Maske; Sozialordnung; Yoruba